Inflammatory gene expression associates with hepatitis B virus cccDNA- but not integrant-derived transcripts in HBeAg negative disease - Magri, A; Harris, JM; D'Arienzo, V; Minisini, R; Jühling, F; Wing, PAC; Rapetti, R; Leutner, M; Testoni, B; Baumert, TF; Zoulim, F; Balfe, P; et al. (MDPI, 2022)
Chronic hepatitis B virus (HBV) infection is a global health problem that presents as a spectrum of liver disease, reflecting an interplay between the virus and the host immune system. HBV genomes exist as episomal covalently closed circular DNA (cccDNA) or chromosomal integrants. The relative contribution of these genomes to the viral transcriptome in chronic hepatitis B (CHB) is not well-understood. We developed a qPCR method to estimate the abundance of HBV cccDNA- and integrant-derived viral transcripts and applied this to a cohort of patients diagnosed with CHB in the HBe antigen negative phase of disease. We noted a variable pattern of HBV transcripts from both DNA templates, with preS1/S2 mRNAs predominating and a significant association between increasing age and the expression of integrant-derived mRNAs, but not with inflammatory status. In contrast, cccDNA-derived transcripts were associated with markers of liver inflammation. Analysis of the inflammatory hepatic transcriptome identified 24 genes significantly associated with cccDNA transcriptional activity. Our study uncovers an immune gene signature that associates with HBV cccDNA transcription and increases our understanding of viral persistence.